Central Bank Communication and Monetary Policy Surprises in Chile - Pescatori, Andrea (IMF Working Papers; Working Paper, 2018)
This paper assesses the quality of the CBC's communication policy by looking at the predictability and effectiveness of monetary policy communications by the Central Bank of Chile (CBC). To do so, we construct indeces of monetary policy surprises for the three major communication channels of the CBC: the release of policy meetings' statements, minutes, and monetary policy reports (IPoM). We assess monetary policy predictability and efficacy by looking at the size and time-evolution of monetary policy surprises associated with meeting statements and the impact of the above communication channels on asset markets. We find that, in general, the CBC's has been effective in its forward guidance through its statements and IPoM. Policy actions are quite predictable, especially post the global financia crisis. The response of equity prices and the exchange rate to monetary policy surprises have the right sign but are not robust. We also find an asymmetric response of equity prices to minutes suggesting that market participants extract information on the status of the economy especially when minutes have a loosening effect. Finally, to look at the macroeconomic impact we find that a 100 bps monetary policy tightening shock implies a decline in economic activity (IMACEC) of about 2 pp. after one year, while the response of inflation is more muted.